The Effect of The Implementation Construction Occupational Health and Safety on The Implementation Time Of The Muaro Mais – Lubuk Gobing Bridge Construction Project Using Smart PLS - Yustisia, Henny; Putri, Nilda Tri; Abdi, Muhammad (Universitas Negeri Padang, 2023)
The high number of work accidents in Indonesia shows that there are still many workers who ignore the issue of Health, Safety, and Environment (HSE) and its implementation procedures because they prefer to work based on experience. In the implementation of the Muaro Mais - LubukGobing Bridge Construction Project, it is necessary to apply HSE in the project environment because of environmental factors that are at risk of causing work accidents such as high rain intensity, the use of heavy equipment, and river flow that can change at any time so that it can be risky for the implementation time of the project. To reduce the rate of work accidents, it is necessary to have a safety system and work health system to create safety and workhealth systems for workers with It is hoped that the construction project can proceed on time. This study aims to determine the effect of the application of HSE on the Muaro Mais – LubukGobing Bridge Construction Project, West Pasaman Regency on the project implementation time by analyzing data using SmartPLS software version 3.2. This research was conducted by distributing questionnaires to workers on bridge construction projects. The results of this study show the Leadership and Administration Indicators of construction service providers (X1) on Punctuality (Y) with a p-value of 0.28 1 > 0.05, a t-statistic value of 1.079 < 1.96, and an original sample O = 0.272. Work Safety Inspection Indicator (X2) against the variable Punctuality (Y) with a p-value of 0.677 > 0.05, t-statistic 0.416 < 1.96, and original sample O = 0.143. Occupational Safety Management Indicator (X3) on Punctuality (Y) with p-value 0.269 > 0.0 5, t-statistic 1.105 < 1.96, and original sample O = 0.272. The R-Square result for the punctuality variable (Y) is 0.198, meaning that the effect of implementing occupational safety and health (X) on punctuality (Y) is 19.8%. The remaining 80.2% was influenced by other factors outside this study.